The screening of Giardia spp. from cow dung in Kuala Pilah / Nurul Nadia Mohamad Zamberi - Mohamad Zamberi, Nurul Nadia (2018)
Parasite can be transmitted to human via animal as the reservoir and this is called as zoonotic transmission. Animal that infected with Giardia spp. will eventually excrete faeces with cyst or trophozoite, thus caused infection in human. This study aims to isolate Giardia spp. cyst from cow dung and to identify the presence of Giardia spp. in cow. Thirty samples of cow dung were randomly collected within Kuala Pilah area then stained with modified Wheatley’s trichrome stain. Ten samples were positives cysts and trophozoites of Giardia spp. Giardia spp. cysts were stained with purple colour and range 10 to 15 μm in oval size. Mature cyst has four nuclei while immature cyst has two nuclei. Trophozoite of Giardia spp. was seen in pear-shaped measuring 12 to 15 μm. Flagella of the trophozoite cannot be seen because it is poorly stain. Until this date, there is no reported study on the presence of Giardia spp. in Kuala Pilah and this result is the evidence that there is a potential outbreak of Giardia spp.